Deep-sea mining ore collection model and pipeline system dynamic analysis - Chen, Wei; Xu, Hai-Liang; Peng, Neng; Hu, Dong; Hao, Qianhua; Xiao, Yongtao (Ocean engineering, 2025)
In the process of deep-sea mining, the movement patterns of seabed mining vehicle and the dynamic characteristics of pipeline systems directly determine ore collection efficiency, system energy consumption, and the operational stability of equipment. Given the current research gaps in the “non-ideal seabed plane” ore collection mode and the dynamic characteristics of pipeline systems, this paper proposes two distinct collection modes—single-collection and obstacle-avoidance collection—based on existing full-area coverage algorithms to adapt to diverse mining environments. For the first time, a dynamic model considering the coupling of ocean flow field-pipeline-mining vehicle was established. Experimental results indicate that this model exhibits good adaptability, with an error margin within 5%. This study investigates the motion responses and dynamic characteristics of pipeline systems under different collection modes. In single-collection mode, the trapezoidal mining method is relatively optimal, as it significantly reduces the force at the connection point between the hose and the mining vehicle while enhancing the stability of the intermediate bin's movement. The acquisition mode has been verified in a deep-sea mining simulation experiment and can improve the stability of the intermediate compartment by 10.6%. In obstacle-avoidance collection mode, the arc-shaped and rectangular collection patterns are relatively ideal motion modes. To improve the stability of the mining system, the distance between the intermediate bin and obstacles should be maximized when designing obstacle-avoidance algorithms. The research methods and conclusions presented in this paper can provide reference and guidance for subsequent scholars to optimize the structure and performance of mining systems under obstacle-avoidance mode. •The paper proposes single collection and obstacle-avoidance collection modes.•Dynamic model considering the coupling of the flow field, pipeline, and collector was established.•The mechanical characteristics of the pipeline and the optimal mining schemes were investigated.